The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1159/000029333
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Uptake and Cardiac Performance in Obese and Normal Subjects during Exercise

Abstract: Work capacity and cardiopulmonary performance were studied in a group of 11 young obese subjects (BMI 39.9 kg/m2) and a group of 10 young normal subjects (BMI 22 kg/m2). First of all they underwent an incremental cycle ergometer test up to exhaustion. Subsequently, every subject of the two groups performed a constant work rate test at different work loads to estimate cardiac output (q̇) below anaerobic threshold (AT) by a 20-second CO2 rebreathing method. Obese subjects had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 18 publications
7
80
1
3
Order By: Relevance
“…[12][13][14][15][16][17] Increased fat mass is associated with decreased exercise performance in overweight children and adolescents. [12][13][14][15][16][17] However, the cause of this limited exercise tolerance remains in question. Several investigators, primarily those who have studied moderately overweight and obese children and adolescents, have reported similar maximal oxygen uptake (V o 2 max) relative to body weight compared with normal-weight control subjects.…”
Section: Results Absolute Ltv O 2 and V O 2 Max And Ltv O 2 As A Permentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17] Increased fat mass is associated with decreased exercise performance in overweight children and adolescents. [12][13][14][15][16][17] However, the cause of this limited exercise tolerance remains in question. Several investigators, primarily those who have studied moderately overweight and obese children and adolescents, have reported similar maximal oxygen uptake (V o 2 max) relative to body weight compared with normal-weight control subjects.…”
Section: Results Absolute Ltv O 2 and V O 2 Max And Ltv O 2 As A Permentioning
confidence: 99%
“…22 Whether these differences significantly influence fitness and performance is unclear. Obesity-related changes in exercise catecholamine response, 15,16,21 myocardial metabolism, and left ventricular morphology 22 may be associated with these findings.We hypothesized that the primary factor limiting severely overweight adolescents when they undertake sustained exercise would be the increased metabolic cost resulting from having to move a greater mass and that there would also be a smaller but still important effect of diminished cardiorespiratory reserve. We predicted that differences in the energy costs of exercise in overweight and nonoverweight adolescents would be demonstrable most clearly during submaximal exercise tasks: compared with nonoverweight adolescents, overweight adolescents would use a larger percentage of their total cardiorespiratory reserve when performing a submaximal task such as "unloaded" pedaling on a stationary bicycle.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Variables used in the existent literature may not thoroughly capture the complexity of disability in obese people. In fact, obese individuals, in association with the increased BMI, show an energetic, cardiac and respiratory, limitation leading to a mobility impairment [45,46], together with the relative reduction of skeletal muscle strength and general deconditioning, also leading to disability [47,48]. Other potential contributors to the disabling status of obese subjects are the friction of the skin through fat depositions on the thighs, the increased plantar foot pressure (first and lesser metatarsal, mid-foot and heel region), as well as the pain and discomfort experienced when performing physical activities [30,[49][50][51].…”
Section: Original Articlementioning
confidence: 99%
“…13,14 The fattest participants would thus have been expected to perform less physical activity during leisure time. However, this hypothesis seems unlikely to explain the differences in LTPA because it has been observed that obese children and adolescents do not have differentiated maximal oxygen consumption capacities but are burdened by the metabolic cost of their excess mass.…”
Section: Relationship Between Ltpa and %Bfmentioning
confidence: 99%